Agriculture in Tanzania since 1986: follower or leader of growth - Delgado, Christopher L.; Minot, Nicholas (World Bank, 2000)
This report is organized in nine parts. In addition to the Executive Summary which outlines the main findings and key messages, Chapter 1 addresses the main agricultural controversies in Tanzania's development strategy. Chapter 2 traces the evolution of public policy affecting agriculture and its impact on the sector's performance; it reviews the evolution of sector policy regimes, from unregulated grain and export markets to cooperative-based marketing to centralized crop authorities and back to relatively unregulated markets. Chapter 3 analyzes the impact of the evolving output price incentives for agricultural production since 1986. Chapter 4 analyzes the costs and returns to crop production. Chapter 5 focuses in greater detail on the controversy of what has actually been the performance of Tanzania's agriculture. Chapter 6 analyzes the extent of rural poverty and the status of food security. Chapter 7 explores the linkages between agriculture and the rest of the economy. Finally, Chapters 8 and 9 summarize the main conclusions and list references, respectively.